Innovative geoelectrical methods for comprehensive groundwater evaluation in East Java, Indonesia - Sri Wahyuni; Gunawan Prayitno; Ikhwan Elhuda; Dian Sisinggih; Kazuyoshi Souma; Wasiska Iyati; Prasetyo Rubiantoro (Results in Engineering)
Effective groundwater exploration is critical for sustainable water resource management, especially in regions with complex geological conditions. This study presents a comprehensive approach to groundwater assessment in Ponorogo, Indonesia, integrating Vertical Electrical Sounding (VES) and Advanced Data Modeling Techniques (ADMT) to improve exploration accuracy. Employing the Schlumberger electrode configuration, VES detected aquiferous layers at 90 to 120 m, with water production rates between 2 and 6 liters per second. ADMT provided enhanced electrical imaging, refining the interpretation of resistivity data and contributing to a more detailed understanding of subsurface hydrogeology. This integrated VES-ADMT methodology addresses gaps in traditional geophysical studies by offering precise, quantitative insights into lithology and aquifer distribution. The findings support improved groundwater management strategies and demonstrate applicability to similar geological formations worldwide, thus advancing the precision of groundwater studies in complex geological contexts.